Avaliações e seus atravessamentos em práticas profissionais de professores de Matemática - Volpato, Leonor Fernanda (2021)
The aim of this work is to investigate how assessments cross the professional practices of teachers who teach mathematics in elementary school. We analyze how teachers deal with external assessments, learning assessment and learning assessment in times of pandemic, in their professional practices. Through interviews carried out with four mathematics teachers, in three moments, we produced readings and discussions in order to analyze effects, practices, processes and assessment crossings in the daily lives of teachers who teach mathematics. The research is qualitative in nature and the theoretical-methodological assumptions are the Semantic Fields Model (MCS) and Oral History (OH). Our main considerations, which were produced throughout our journeys, through the textualizations of the interviews we conducted and our discussions about school evaluations, are: a) effects of external evaluations that control, shape and direct political-pedagogical practice of the teacher; b) in few possibilities of interactions between professor and students, during the months of remote teaching, which resulted in a basically bureaucratic evaluation that offered little potential to regulate teaching and learning processes. Mathematically educating Basic Education students in times of pandemic was something challenging for teachers, with immediate demands and urgencies without much time for planning. Assessments occupied an important and intriguing space in the professional practices of these teachers who teach mathematics.